Protective function of the emotional abilities for prevention of alcohol consump- tion and smoking: An intervention proposal - Fernández, Belén; Jorge, Vanesa; Bejar, Eva (Psicooncología, 2009)
Tobacco and alcohol use in the Spanish young people is one of the most elevated in Europe. In Spain, the early beginning in these drugs use is especially worrying and it turns into a first magnitude public health problem. In this background, educative and preventive actions directed to youngest groups become essential. It’s necessary to affect the development of projects, plans and campaigns to break the present tendencies of tobacco and alcohol use among young people. This article reviews the studies that have analyzed the relationship among Emotional Intelligence and tobacco and alcohol use. Different works show clearly that emotional abilities are a protective element faced whit the use of these substances. We enhance the great relevance for the development of preventive programs based on Emotional Intelligence Model and we show an intervention proposal to develop in the educative field with children from 7 to 9 years.
Keywords: Tobacco; Alcohol; Emocional intelligence; Emotion; Prevention